A ribonuclease from human skeletal muscle - Goldspink, D. F. (1970)
1. A ribonuclease has been prepared from human muscle by ammonium sulphate fractionation, heat treatment and ion-exchange chromatography. 2. The enzyme degrades polycytidylic acid and polyuridylic acid to the nucleoside 3′-phosphates, with nucleoside 2′:3′-cyclic phosphates as intermediates. Polyadenylic acid and polyguanylic acid are not attacked. 3. The enzyme has maximal activity at pH8.5. The molecular weight (by gel filtration) is between 11000 and 12000. It is relatively heat-stable. It exhibits optimum activity in a medium of high ionic strength, and is inhibited by several bivalent cations, particularly Zn(2+).